Impact of the fibre manufacturing quality control on the fibre pullout performance - Cunha, Vitor M. C. F. (2008)
The effectiveness of a given fibre as a medium of stress transfer is often assessed using a single fibre pullout test, where fibre slip is monitored as a function of the applied load to the fibre. Over the past 30 years, so-called improved shaped fibres have been brought onto the market by different producers with claimed better performances than straight fibres. Nowadays, the most commonly used fibres have anchorage mechanisms. Generally, these fibres are produced by mechanically deforming the fibre with a hook, cone or paddle adjacent to each of its ends. Nevertheless, due to different materials and manufacturing processes, the mechanical properties such as, tensile strength and grade of mechanical anchorage differ amongst different producers, even for the same fibre type. These differences have an effect on the fibre pullout behaviour and, consequently, in the overall behaviour of FRC under loading. In the present work, a comparative study of three hook-ends fibres from different producers is carried out. The statistical variation of the fibre geometry dimensions is assessed, and its influence on the fibre mechanical properties is ascertained. Experimental tensile and pullout tests results of each fibre brand are presented and discussed.